Recent Advances in Strategies to Combat Bacterial Drug Resistance: Antimicrobial Materials and Drug Delivery Systems - Yao, Jiaxin; Zou, Pengfei; Cui, Yanan; Quan, Liangzhu; Gao, Chunsheng; Li, Zhiping; Gong, Wei; Yang, Meiyan (Pharmaceutics, 2023)
Bacterial infection is a common clinical disease. Antibiotics have saved countless lives since their discovery and are a powerful weapon in the fight against bacteria. However, with the widespread use of antibiotics, the problem of drug resistance now poses a great threat to human health. In recent years, studies have investigated approaches to combat bacterial resistance. Several antimicrobial materials and drug delivery systems have emerged as promising strategies. Nano-drug delivery systems for antibiotics can reduce the resistance to antibiotics and extend the lifespan of novel antibiotics, and they allow targeting drug delivery compared to conventional antibiotics. This review highlights the mechanistic insights of using different strategies to combat drug-resistant bacteria and summarizes the recent advancements in antimicrobial materials and drug delivery systems for different carriers. Furthermore, the fundamental properties of combating antimicrobial resistance are discussed, and the current challenges and future perspectives in this field are proposed.